The Effect of Basic Life Support Course on Community Knowledge Level - I Kadek Artawan; Yupin Aungsuroch; I Gede Juanamasta; I Made Sukma Wijaya; Komang Agus Jerry Widyanata (Babali Health, 2021)
Introduction: Cardiac arrest is the most pre-hospital emergency cases. Approximately 30.000 people have cardiac arrest in pre-hospital and about 33% have treated with bystander. Basic life support (BLS) with cardiopulmonary resuscitation (CPR) is a first aid procedure that needs to be performed in this case. Death could occur within minutes if the first aid does not adequately performed. The study aimed to know the effect of BLS courses on the community knowledge level in the North Denpasar District. Methods: The study was a pre-experimental study with a pre-posttest design. Study participant selected by cluster random sampling technique and 199 participants chosen as study participants. To collect the community knowledge data, a questionnaire employed in this study. American Heart Association (AHA) guideline for the public published in 2015 enrolled as a reference in organizing ten questions in the questionnaire with Guttman Scale. Results: The characteristics of respondents were 27% participants were aged between 30-39 years, 56% graduated from senior high school, 55% work as employees and 90% never attended BLS training program. There was a significant mean difference from the pre-test and post-test data. The mean difference before and after the BLS course were 8.38 and 9.74, respectively. There was a significant correlation between the BLS course and the level of knowledge (p = 0.000). Conclusion: The level of knowledge about BLS before the course was 63%. It classified into a good knowledge level. The level of knowledge about BLS after the course was significantly improved. It increased to 97.5%.